Evaluating online health information utilisation and its psychosocial implications among breast cancer survivors: Qualitative explorations - Samar J Melhem; Shereen Nanhani-Gebara; Reem Kayyali (Tabriz University of Medical Sciences, 2024)
Background: This study investigated the online information-seeking behaviours of breast cancer patients at Jordan University Hospital, focusing on their dissatisfaction with available online health resources and its impact on their well-being and anxiety levels. Methods: Employing descriptive phenomenology and convenience sampling, we conducted five Skype-based focus groups with 4-6 breast cancer survivors each, from March to July 2020. Data analysis was performed using NVivo, following Braun and Clark's inductive thematic analysis framework. Results: The thematic analysis revealed critical insights into survivors' interactions with online cancer resources, identifying key subthemes such as the quality of online information, cyberchondriasis, health literacy and search strategies, the distress caused by counterproductive searches, and the tendency to avoid internet searches. Conclusion: The study underscores the challenges breast cancer survivors face in accessing online health information, especially in Arabic. It highlights the need to improve the quality and accessibility of these resources. Enhancing the cultural relevance of online materials and educating patients on effective information evaluation are crucial. These measures can significantly boost health literacy, mitigate anxiety, and provide better support for breast cancer survivors.